Some possible effects of common agricultural policy (CAP) on Romanian agriculture during the 2014 - 2020 financial perspective: How much does the paradigm really change? - Jean Andrei; Dorel Dusmanescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Common Agricultural Policy has a major impact on the Romanian agricultural sector, being one of the most important European policies affecting such an important part of the economy and population, and now it is passes through a new reform. Reconsidering the perspective of Common Agricultural Policy (CAP) during the next financial framework 2014-2020, will impose new conditions, both in the European agricultural sector reform and to the Romanian one as well, including adaptation to the new realities imposed by the CAP philosophy. The paper presents a short analysis regarding the possible effects on the Romanian agriculture in the perspective of the new CAP reforms, taking into account two main aspects: reform of direct payments system and the greening measures adopted for 1st CAP Pillar.
Keywords: 330; agriculture; budget; CAP reform; greening; direct payments